Lithium Storage in Carbon Cloth–Supported KNb3O8 Nanorods Toward a High‐Performance Lithium‐Ion Capacitor. Issue 8 (11th May 2021) - Sun, Hui; Niu, Fei; Yuan, Peng; He, Xuexia; Sun, Jie; Liu, Zonghuai; Li, Qi; Lei, Zhibin
Abstract : Exploration of novel anodes with a high capacity and fast charge rate is crucial for developing high‐energy‐density lithium‐ion capacitors. Herein, high‐rate Li + insertion into KNb3 O8 nanorods grown on conductive carbon cloth (CC) by a facile electrodeposition technique is reported. The hierarchically porous network and the enhanced conductivity enable the CC‐KNb3 O8 electrode to deliver a high discharge capacity of 271 mA h g −1 at 0.01 A g −1 with a low yet safe voltage (1.2 V versus Li/Li + ) while exhibiting outstanding cycling stability (225 mA h g −1 after 100 cycles) and superior rate capability (159 mA h g −1 at 0.5 A g −1 ). Electrochemical results and X‐ray photoelectron spectroscopy (XPS) analysis show that accompanying mutielectron transfers involving the Nb 5+ /Nb 4+ and Nb 4+ /Nb 3+ redox reactions, KNb3 O8 remains in the stable orthorhombic phase without notable volume expansion during the whole charging and discharging process. A lithium‐ion capacitor built with a CC‐KNb3 O8 anode and active carbon cathode delivers a maximum energy density of 69 W h kg −1 at a power output of 346 W kg −1 and retains 88% capacity after 1000 cycles at 2.0 A g −1 . This work opens up a new avenue for designing high‐capacity niobium‐based electrodes toward a high‐performance charge storage device. Abstract : KNb3 O8 nanorods have been successfully grown on carbon cloth (CC) by electrodeposition and thermal annealing treatment. The short ion diffusion pathway, large Li + diffusion coefficient, and good conductivity enable fast Li + storage in KNb3 O8 without notable phase change and volume expansion. A Li‐ion capacitor built with a CC‐KNb3 O8 electrode displays a high energy density, good cycling stability, and Coulombic efficiency.